Distribution Network Flexibility Evaluation Method Considering Collaborative Interaction of Flexible Resources - Zhiwen LIU; Yan LI; Chong SHAO; Xinming FAN; Qinghui ZENG (Zhongguo dianli, 2024)
A distribution network flexibility evaluation method considering collaborative interaction of flexible resources is proposed. Firstly, a flexibility evaluation indicator system is constructed, which includes three aspects: collaborative regulation capacity, collaborative efficiency quality, and power grid reliability. Secondly, a Gaussian mixture model is used to construct typical operating scenarios, and the subjective and objective weights of evaluation indicators are determined using Analytic Hierarchy Process and Random Forest Model, respectively. Through a double-layer evaluation process, the evaluation indicator values for each typical scenario are calculated. Then, based on the probability of typical scenarios appearing, the comprehensive flexibility evaluation index values of each flexible resource access scheme are weighted. Finally, the feasibility and effectiveness of the proposed method are verified through the case study on a 54-bus distribution network.